“Comportamiento Agronómico Del Hartón (Musácea Paradisiaca) Con La Aplicación De Dos Abonos Orgánicos En El Recinto Garza Grande”. - Alcívar Cansiong, Juseth Bryan (2021)
The present investigation was carried out in the Mocache canton in the Los Ríos Province in the Garza Grande sector, in an established plantain crop of the hartón variety, which had as its main objective “To evaluate the agronomic behavior of the hartón crop (Musácea paradisiaca) with the application of organic fertilizers in the Garza Grande area”. For this purpose, the study set out a completely randomized experimental design with 4 treatments and 4 repetitions, applying a statistical analysis with the Tukey test at 5% probability.The fertilizers used in this work were urea, humus and compost, whose doses were established with the help of a soil analysis, with which the respective fertilization plan was elaborated, leaving as follows: T0 conventional control (Urea) 82.4 g; T1 humus 2530 g; T2 compost 1650 g; T3 humus + compost 1300 + 800 g. To fulfill the objective set out in the research, the variables were established: plant height, stem diameter, number of leaves, bunch weight, number of hands per bunch, fruit length, fruit diameter and yield. The results obtained in the present study were: in plant height 2.85 m, stem diameter 63.50 cm, number of hands per bunch 6. Number of leaves in T3 with 8.10 and in finger length center of hand 12 inches; in bunch weight with 9.2 kg. and fruit diameter 14, 8 with humus.